Rock powders in the soil-plant system: mineralogy and microbiome response - Reis, Betania Roqueto dos (2020)
Rock powders are only ground and sieved rocks, usually co-products of the mining and crushing industry, which can be used in agriculture in accordance with Federal Law 12,890. Field observations and experiments have shown results incompatible with the amount and kinetics of nutrient release by rock powders. These results suggest that the approach to remineralization by an exclusively chemical-inorganic perspective is not sufficient to understand and predict the functioning of the system. Mineral dissolution is fundamental to regulate CO2 contents, soil chemical and physical characteristics and energy source for microorganisms. It is known that the interaction of rocks/minerals and microorganisms occurs since before the formation of soils and that the colonization of the terrestrial Earth by plants was possible due to the interaction of microorganisms and primitive roots to obtain nutrients from non-soluble sources. These interactions are responsible for numerous processes among soil and them, including weathering and pedogenesis, fundamental for soil formation. The objective of this project was to understand the interaction of rock powders with the microbial community in the system (soil + RM)-plant. The experiment was developed with five distinct sources of rock powders (one Fonolith, three types of Basalt and one Granite) and one soluble source of potassium fertilizer (KCl) in pots cultivated with Brachiaria brizantha cv. Marandu. The experiment was assembled into copies to monitor system changes over time. The following were evaluated: enzymatic activity and alteration of the soil microbial community, colonization by arbuscular mycorrhizal fungi (AMF), mineralogical alterations, quantification of dissolution and release of nutrients from rock powders. In this chapter we present the results of the structuring of the bacterial community over eight months by the T-RFLP fingerprinting technique and how the leached elements aid in this modification. In general, the bacterial community changes slowly in treatments with rock powders, differentiating in eight months, and is structured according to the applied rock. The bacterial community for treatment with soluble source is already restructured after 1 month of application, influenced by the release of K and Ca ions.